2007
DOI: 10.7773/cm.v33i3.1170
|View full text |Cite
|
Sign up to set email alerts
|

Hydrography at the North Mouth of La Paz Bay, Baja California Sur, Mexico

Abstract: , en particular en su parte profunda, se encuentran muy influenciadas por la variabilidad del sur del Golfo de California (Obeso-Nibelas 2003). A su vez, el Golfo de California se acopla a la variabilidad ambiental interanual de gran escala del Pacífico Oriental, lo cual ha podido ser identificado en series de tiempo del nivel del mar y anomalías de temperatura en la costa (Durazo et al. 2005, Jiménez-Illescas 1996).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 7 publications
1
8
0
4
Order By: Relevance
“…The EOF 2 of Chl-a ( Fig. 7d) explained 31% of the variance; high values were observed mainly along the coast, which suggests upwelling events associated to strong local atmospheric forcing (northwesterly surface wind) could be generating advection and strong coastal currents mainly during the winter period (Obeso- Nieblas et al, 2007). Both patterns were similar to those shown from winter to summer in Chl-a average seasonal anomalies (Fig.…”
Section: Resultssupporting
confidence: 67%
“…The EOF 2 of Chl-a ( Fig. 7d) explained 31% of the variance; high values were observed mainly along the coast, which suggests upwelling events associated to strong local atmospheric forcing (northwesterly surface wind) could be generating advection and strong coastal currents mainly during the winter period (Obeso- Nieblas et al, 2007). Both patterns were similar to those shown from winter to summer in Chl-a average seasonal anomalies (Fig.…”
Section: Resultssupporting
confidence: 67%
“…Because of its shallow sill (~320 m) (Nava- Sánchez et al 2001), NPIW does not enter Alfonso Basin (confirmed also by Obeso-Nieblas et al 2007), so the variations found in the sedimentary δ 15 N of this zone might be associated with changes in SSW and to variations induced by climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Debido a su umbral somero (~320 m) (Nava- Sánchez et al 2001), el AIPN no ingresa a la cuenca Alfonso (confirmado también por Obeso-Nieblas et al 2007), por lo que las variaciones de δ 15 N sedimentario en esta zona pueden estar asociadas con los cambios en ASS y con variaciones inducidas por el cambio climático.…”
Section: Introductionunclassified
“…En la figura 11 se plantea un escenario en donde se muestran los valores mínimo y máximo para bahía de La Paz, BCS y los cambios en la salinidad por intrusión de Agua del Golfo de California (AGC) y Agua Superficial Ecuatorial (ASE) (Obeso-Nieblas et al, 2007); además, se plantea el escenario hipotético donde se suma la diferencia entre las dos masas de agua, como límite superior e inferior (±0.43) donde se observa cambios taxocenóticos relacionados con la intrusión de las dos masas de agua a partir de 35.5.…”
Section: Resultsunclassified